The relationship between neighborhood environment and physical activity: a case study in USJ, Subang Jaya, Selangor, Malaysia - Siti Nur Afiqah Mohamed Musthafa,; Ling, Oliver Hoon Leh; Marlyana Azzayati Marzukhi,; Yusfida Ayu Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Human health and well-being have the potential to be improved through contact with nature and green exercise or outdoor activity. Thus, one of the important contributions of environmental health to human well-being lies in the provision of safe resources (water, air, food) and a safe environment (home/neighborhood, work, leisure) within which society and individuals can thrive. This paper discusses the association between the USJ residents’ perception of their neighborhood’s (outdoor) environment and their physical activity involvement. The neighborhood environment and physical activity involvement were identified through a questionnaire survey. A stratified random sampling technique was used with 385 respondents from a total of 156,011 numbers of the population in Subang Jaya. The data were analyzed using frequency and regression analysis and it showed that the neighborhood’s environment has no significant effect on the involvement of physical activity among the residents in USJ (respondents). The result was the opposite of the other researchers who have found links between the neighborhood’s built-environment characteristics and physical activity (such as mixed land use, which indicates having destinations such as restaurants and shops nearby). This may be because the respondents were exposed to the neighborhood’s environment more frequently when engaging in physical activity, which increased their unhappiness with the neighborhood’s quality. Furthermore, the majority of respondents indicated that they typically engaged in indoor physical exercise. It is hoped that through this study, park managers and developers may come out with more exciting features or concepts in their future development to help encourage more physical activity involvement among the residents toward better health.